Recria de tilápia do nilo (Oreochromis niloticus) com spirulina (Arthrospira platensis) em tanques de ferrocimento - Ribeiro, Diego Castro (2019)
Interaction between Nile tilapia (Oreochromis niloticus) and spirulina (Arthrospira platensis) can generate many benefits for fish, especially in the early stages of the life cycle. Thus, the objective was the viability of a Nile tilapia rearing with spirulina in ferrocement tanks with brackish water recirculation. The field experiment was conducted on a pilot scale for 43 days, with the stocking of newly reverted fingerlings (0.8 g) in salinity water 10 at the density of 200 fish/m³. Three cultivation modules were constructed in which three different food managements were used: M1 – 100% of the supply of fish feed in clear water; M2 – 50% of the fish feed in spirulina Waters; and M3 – without supply of fish feed in spirulina waters. In the culture, the zootechnical performance of the fish was analyzed, as well as the water quality. After this period, the health of the culture was verified through the evaluation of hematological parameters of the blood and the incorporation or not of glycosaminoglycans (GAGs) in the skin matrix of the fish. An assessment was also made of the financial viability of fish rearing. The ferrocement structure was easy to construct and low cost, besides facilitating the recirculation of the water allowing its reuse. The M2 treatment presented the best zootechnical performance at the end of breeding, with 98.6% survival and apparent feed conversion of 0.52:1, due to the beneficial interaction between fish and microalgae, leaving the levels of pH, alkalinity, hardness, nitrogen and phosphates within the comfort range for the species in the worked salinity. Spirulina increased hemoglobin, erythrocytes and total leukocytes, making M2 the highest hematimetric indexes. Quantity of GAGs grew with the greater participation of spirulina in the diet, with an addition of up to 115%, making tilapia skin potentially more effective in the treatment of burns. Financial analysis showed a fairly viable breeding venture, with a cost-benefit ratio of 1.66 and a leveling point of 26.42%, having refunded the amount invested in 1.45 years despite the production cost of US$ 1.47 kg of fish. The rearing of Nile tilapia with spirulina in brackish water is feasible even by reducing the amount of artificial feed in half as a function of the supplementation of live spirulina in the water, that improves fish sanity and increases the healing potential of its skin.